Discovery of novel S1P2 antagonists, part 3: Improving the oral bioavailability of a series of 1, 3-bis(aryloxy)benzene derivatives. Issue 4 (15th February 2016) - Kusumi, Kensuke; Shinozaki, Koji; Yamaura, Yoshiyuki; Hashimoto, Ai; Kurata, Haruto; Naganawa, Atsushi; Otsuki, Kazuhiro; Matsushita, Takeshi; Sekiguchi, Tetsuya; Kakuuchi, Akito; Yamamoto, Hiroshi; Seko, Takuya
Graphical abstract: Abstract: The structure of the S1P2 antagonist1 has been modified with the aim of improving its oral bioavailability. The chemical modification of the alkyl chain and carboxylic acid moieties of1 led to significant improvements in the oral exposure of compounds belonging to this series. The optimization of the ring size of the urea portion of these molecules also led to remarkable improvements in the oral exposure. Based on these changes, the pyrrolidine derivative16 was identified as a suitable candidate compound and showed excellent pharmacokinetic profiles in rat and dog, while maintaining high levels of potency and selective antagonistic activity toward S1P2 .